AlGaN/GaN MIS-HEMTs with a p-GaN Cap Layer. (28th December 2017) - Hsu, Che-Ching; Shen, Pei-Chien; Zhong, Yi-Nan; Hsin, Yue-Ming
ABSTRACT: In this study, AlGaN/GaN MIS-HEMTs with a p-GaN cap layer and ALD deposited Al2 O3 gate insulator were fabricated. Devices with two different thicknesses of p-GaN cap layers were investigated and compared. AlGaN/GaN MIS-HEMT with an 8-nm p-GaN cap showed a better DC characteristics than device with a 5-nm p-GaN cap. The drain current of 662.9 mA/mm, a high on/off current ratio of 2.67×10 9 and a breakdown voltage of 672 V were measured in device with an 8-nm p-GaN cap. In addition, lateral leakage current was investigated by using adjacent MIS gate structures with a separation of 3 μm to investigate the leakage current.